Self-presentation of elderly internet celebrity on Douyin in China - Yan, Zhang; Alsagoff, Syed Agil; Yasin, Megat Al Imran (Redfame Publishing, 2024)
With the rapid development of mass media and an increase the aging population in China,more elderly people are actively using the internet. Douyin, owned by ByteDance, is one of the fastest growing apps in China. Many elderly users use this app for entertainment and information sharing. Currently, there is an emergency of several elderly internet celebrities.The study investigated how elderly internet celebrities in China used short videos to present themselves and shape their image on Douyin. The study employs literature analysis and content analysis to analyzes the content of short videos of 10 elderly internet celebrities on Douyin. The study summarized the self-presentation characteristics of elderly internet celebrities,dismissed stereotypes regarding elderly people and recommended new ideas and paths for the governance of China's aging society.